Biological activity of dolichandrone serrulata flowers and their active components - Phanida Phanthong (2018)
Dolichandrone serrulata (DC.) Seem flowers are widely used as vegetables in northern and eastern Thailand. Biological studies of the methanolic extract of these flowers have shown promising antioxidant activity. Biological-guided separation of D. serrulata flowers yielded six compounds, identified as hallerone, protocatechuic acid, rengyolone, cleroindicin B, ixoside, and isomaltose. This is the first report on hallerone, protocatechuic acid, rengyolone, cleroindicin B, and isomaltose in D. serrulata. Protocatechuic acid was the most potent scavenger of 2,2-diphenyl-l-picrylhydrazyl and hydroxyl radicals with IC 50 values of 25.6 ± 0.6 and 29.6 ± 0.4 μM, respectively. Hallerone and rengyolone showed moderate scavenging action on superoxide radicals and inhibited H 2 O 2 induced reactive oxygen species production in HEK-293 cell. In addition, the other isolated compounds showed weak activity.